Analytical Techniques for Analyzing Thermally Degraded Monoethylene Glycol with Methyl Diethanolamine and Film Formation Corrosion Inhibitor - AlHarooni, K.; Pack, David; Iglauer, Stefan; Gubner, R.; Ghodkay, V.; Barifcani, A. (American Chemical Society, 2016)
Gas hydrate blockage and corrosion are two major fl ow assurance problems associated with transportation of wet gas through carbon steel pipelines. To reduce these risks, various chemicals are used. Monoethylene glycol (MEG) is injected as a hydrate inhibitor while methyl diethanolamine (MDEA) and fi lm-forming corrosion inhibitor (FFCI) are injected as corrosion inhibitors. A large amount of MEG is used in the field, which imposes the need for MEG regeneration. During MEG regeneration, rich MEG undergoes thermal exposure by distillation to remove the water. This study focuses on analyzing the kinetics of methane gas hydrate with thermally exposed MEG solutions with corrosion inhibitors at 135 − 200 ° C. The study analyses the hydrate inhibition performance of three different solutions at selected concentrations and pressures (50 − 300 bar), using a PVT cell and isobaric method. Results established that thermally degraded solutions cause hydrate inhibition drop. However, the inhibition drop was found to be lower than that of pure thermally degraded MEG, which is caused by the additional hydrate inhibition effects of MDEA and FFCI. In addition, hydrate phase boundaries and regression functions were reported to provide a deep insight into the operating envelope of thermally degraded MEG solutions.